Pengembangan Media Pembelajaran Menggunakan Uno Stacko Pada Materi Fisika Kelas X - Siti Ayu Kumala; Ria Asep Sumarni; Fita Widiyatun (Navigation Physics : Journal of Physics Education, 2020)
The UNO stacko game, is a game that is being loved by many people both of children and adults. In this study, The UNO game that will be developed is the UNO stacko game as a learning media. The UNO stacko game consists of 45 stackos with various colors and various command instructions. The colors in UNO stacko have five colors, including blue, yellow, red, green, and purple. Each color block is filled with test questions for understanding physics matter that are in accordance with the game instructions. Validation tests are carried out by media experts and material experts, where in each validation test there are several aspects tested. The average results from the results of validation tests of media experts and material experts regarding this interactive learning media were 88.19% and 88.69%. This percentage shows that interactive learning media that researchers make is included in good criteria. So this media can be used as a learning media that can be applied to physics learning for students.